The narrative on rural youth and economic opportunities in Africa: facts, myths, and gaps - Mabiso, Athur; Benfica, Rui (International Fund for Agricultural Development, 2019)
A narrative on rural youth in Africa has continued to evolve in policy circles around the world. Much of it is driven by population statistics that point to an imminent youth bulge in Africa and concerns about economic stagnation for the continent. This paper reviews the narrative on rural youth and economic opportunities in Africa, using a set of policy documents from various African countries and regional and international organizations. Since large numbers of African rural youth are predicted to enter the agrifood system in the coming decades, there is a growing need for more investments in African agriculture to enhance the prospects of rural youth. While the evidence does show that African youth are indeed more educated than their parents and previous generations, several constraints on the level and quality of learning in rural Africa are raised.